Penerapan Model Pembelajaran Conceptual Understanding Procedures Dapat Meningkatkan Hasil Belajar Matematika Siswa di Kelas IX SMP - fatimah Sari; Susi Sulastri Lubis; Andi Saputra Mandopa (JURNAL CERMATIKA, 2025)
This research was carried out at SMP Negeri 3 Angkola Timur. The subjects in this research were students in class IX-2 of SMP Negeri 3 East Angkola for the 2023-2024 academic year, totaling 20 students. The object of this research is the application of the Conceptual Understanding Procedures learning model to the sub-subject of cubes and blocks. From the results of the first cycle of observations, it is known that at the first meeting the observation results were 65.5 and the observation results at the second meeting were 75 with an average of 71.25%. Meanwhile, the results of the second cycle of observations showed that at the third meeting the observation results were 80 and the observation results at the fourth meeting were 87.5 with an average of 77.5%. The results of the initial test obtained an average score of 55% with 25% or 5 students completing their studies, while 75% or 15 students did not complete their studies. After taking action in cycle I in class IX-2, carrying out the first learning outcomes test, the average score in cycle I was 65.25, 13 students or 65% completed their studies, while 7 students or 35% did not complete their studies. In cycle II in class IX-2, the implementation of the first cycle learning outcomes test obtained an average score of 74.5, 17 students who completed their studies or 85%, while those who did not complete their studies were 3 people or 15%. By implementing the Conceptual Understanding Procedures learning model, students' mathematics learning outcomes can be improved.